Cardiovascular events in patients with COPD: TORCH Study results. Issue 8 (4th August 2010) - Calverley, Peter M A; Anderson, Julie A; Celli, Bartolome; Ferguson, Gary T; Jenkins, Christine; Jones, Paul W; Crim, Courtney; Willits, Lisa R; Yates, Julie C; Vestbo, Jørgen
Abstract : Background: Previous studies have suggested that long-term use of β agonists to treat chronic obstructive pulmonary disease (COPD) may increase the risk of cardiovascular adverse events. In this post hoc analysis, data from the TOwards a Revolution in COPD Health (TORCH) study were used to investigate whether use of the long-acting β2 agonist salmeterol over 3 years increased the risk of cardiovascular adverse events in patients with moderate to severe COPD. Methods: TORCH was a randomised, double-blind, placebo controlled study conducted at 444 centres in 42 countries. Patients (n=6184; safety population) received twice daily combined salmeterol 50 μg plus fluticasone propionate 500 μg (SFC), either component alone, or placebo. Adverse events were recorded every 12 weeks for 3 years. Results: The probability of having a cardiovascular adverse event by 3 years was 24.2% for placebo, 22.7% for salmeterol, 24.3% for fluticasone propionate and 20.8% for SFC. Although a history of myocardial infarction doubled the probability of cardiovascular adverse events, the event rates remained similar across treatment groups. Conclusion: Post hoc analysis of the 3-year TORCH dataset showed that salmeterol alone or in combination (SFC) did not increase the risk of cardiovascular events in patients with moderate to severe COPD.